Method for preparing acetaldehyde by dehydrogenation of ethanol
By using multi -phase CUSN dual -metal catalysts, the problem of low selectivity and short service life of catalyst products in existing technologies, realizing efficient preparation of acetaldehyde and co -produced hydrogen, with good stability and economy.
Patent Information
- Application Number
- CN202111400665.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-11-24
AI Technical Summary
In the existing methods for direct dehydrogenation of ethanol to prepare acetaldehyde, the catalyst has low product selectivity and many reaction by-products, which leads to difficulty in subsequent separation, and the metal components and the support are not strongly interacting, resulting in a short catalyst service life.
A heterogeneous CuSn bimetallic catalyst is used to prepare the catalyst through a co-precipitation method. The catalyst is composed of Cu, Sn active metals and catalytic promoters Al, Zr, and Si. It is filled in the reaction tube of the fixed-bed reactor. The reaction temperature is 250 to 450°C. ℃.
It improves the selectivity of acetaldehyde, reaching 99%, at the same time, hydrogen production, high atomic economy, good catalyst stability, and long service life.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing acetaldehyde, and in particular to a method for preparing acetaldehyde by using ethanol as a reactant through a direct dehydrogenation process. Background Art
[0002] Acetaldehyde is an important aliphatic compound, which is widely used in agriculture, industry and daily life. It is the raw material for producing important chemicals such as acetic acid, n-butanol and ethyl acetate, and has high application value. At present, the main synthetic routes of acetaldehyde include ethylene oxidation, acetylene hydration, acetic acid reduction, ethane oxidation, CH4 and CO synthesis, ethanol oxidation, and ethanol dehydrogenation. my country mainly uses ethylene oxidation, and acetaldehyde prepared by ethylene oxidation accounts for about 68% of the total output. However, the above-mentioned synthetic routes of acetaldehyde have problems such as corrosion of equipment, environmental pollution and low atomic economy. In comparison, the preparation of acetaldehyde using ethanol as raw material has certain technical advantages. This method has the advantages of mild reaction conditions, high atomic economy and environmental friendliness, showing great development potential. In recent years, the production of bioethanol in my country has increased year by year, especially the commercialization of coal-based ethanol technology of Dalian Institute of Chemical Physics, which has provided a richer source of ethanol and laid the foundation for the further downstream high-value utilization of ethanol. The route of preparing acetaldehyde by direct dehydrogenation of ethanol and producing hydrogen as a by-product meets the requirements of sustainable energy development. In addition, this method has the advantages of mild reaction conditions, high atom economy, environmental friendliness, and easy separation of gas and liquid, making it an ideal acetaldehyde production route.
[0003] At present, the Cu / SiO2 catalyst used in the direct dehydrogenation of ethanol to prepare acetaldehyde has the problem of low product selectivity. The conversion rate of ethanol dehydrogenation at 280°C is 49%, and the acetaldehyde selectivity is 69%. There are many types of reaction by-products, which have an impact on subsequent separation. In addition, the metal component and the carrier do not interact strongly, and are easily sintered and agglomerated, which shortens its service life. Therefore, it is of great significance to develop a solid catalyst system that is easy to prepare, highly reactive and stable. Summary of the invention
[0004] The significance of the present invention is to overcome the shortcomings of the current process of preparing acetaldehyde by direct dehydrogenation of ethanol. The preparation method has a simple reaction process, a high selectivity of the catalyst for acetaldehyde, good stability and long life.
[0005] The acetaldehyde involved in the present invention is prepared by the following scheme.
[0006] Ethanol is used as a raw material and reacted in a fixed bed reactor. After a multiphase CuSn bimetallic catalyst is filled in a reaction tube, the reaction tube is placed in the fixed bed reactor, and the reaction temperature is 250-450°C. The multiphase CuSn bimetallic catalyst is composed of Cu, Sn active metals and a catalytic promoter, wherein the catalytic promoter is one or more of Al, Zr, and Si; the multiphase CuSn bimetallic catalyst is composed of Cu, Sn active metals and a catalytic promoter, wherein the catalytic promoter is one or more of Al and Zr; the multiphase CuSn bimetallic catalyst has an active metal Cu content of 5wt% to 35% (by weight); and a metal Sn content of 2% to 20% (by weight); the catalyst bed thickness filled in the reaction tube is 5cm to 30cm, the reaction is at normal pressure, and the feed mass space velocity of ethanol is 0.5 to 3.5h -1 The preferred reaction conditions are: the catalyst bed thickness in the reaction tube is 10 cm to 25 cm, the ethanol feed mass space velocity is 0.5 to 3.5 h -1 The ethanol may be anhydrous ethanol or an ethanol aqueous solution, and the water content is 1.0% to 10% (by weight). The reaction temperature of the ethanol dehydrogenation to acetaldehyde is 280 to 330°C.
[0007] The multiphase CuSn bimetallic catalyst for catalytic dehydrogenation of ethanol to produce acetaldehyde has the following characteristics: (1) The introduction of Sn partially inhibits the dehydrogenation activity of Cu, avoiding excessive dehydrogenation of ethanol, thereby improving the selectivity of acetaldehyde; (2) The introduction of Sn disperses the active Cu species, avoiding the sintering of Cu ions during the reaction, inhibiting deactivation, and improving stability; (3) The Sn species itself has moderate dehydrogenation activity, which can catalyze the dehydrogenation of ethanol and improve the overall catalytic activity of the CuSn bimetallic catalyst.
[0008] The advantages of this method are: (1) The CuSn bimetallic catalyst is simple to prepare and can catalyze the reaction efficiently. The catalyst activation and regeneration can be completed by simple calcination and reduction operations. (2) The catalytic system has certain advantages in the process of catalyzing the dehydrogenation of ethanol to produce acetaldehyde. The selectivity of the target product is as high as 99%, and hydrogen is co-produced at the same time, with high atom economy. DETAILED DESCRIPTION
[0009] In order to further explain the present invention in detail, several specific implementation cases are given below, but the present invention is not limited to these embodiments.
[0010] The reaction is carried out in a fixed bed reactor, and the reaction tube is filled with a catalyst and then placed in the fixed bed reactor;
[0011] Example 1
[0012] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. Screen the catalyst with 14-25 mesh and fill it into the reaction tube, fill a 10cm bed, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 60% and the selectivity of acetaldehyde was 99%.
[0013] Example 2
[0014] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. Screen the catalyst with 14-25 mesh and fill it into the reaction tube, fill a 12cm bed, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 65% and the selectivity of acetaldehyde was 97%.
[0015] Example 3
[0016] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 0.5h -1The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 72% and the selectivity of acetaldehyde was 89%.
[0017] Example 4
[0018] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. Screen the catalyst with 14-25 mesh and fill it into the reaction tube, fill a 10cm bed, and the mass space velocity of the raw ethanol is 3.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 49% and the selectivity of acetaldehyde was 98%.
[0019] Example 5
[0020] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. Screen the catalyst with 14-25 mesh and fill it into the reaction tube, fill a 10cm bed, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 280°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 57% and the selectivity of acetaldehyde was 98%.
[0021] Example 6
[0022] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 0.5h -1 The reaction was carried out at 330°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 69% and the selectivity of acetaldehyde was 96%.
[0023] Example 7
[0024] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 0.5h -1 The reaction was carried out at 350°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 75% and the selectivity of acetaldehyde was 91%.
[0025] Example 8
[0026] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed, the water content of the raw ethanol is 5wt%, and the mass space velocity of ethanol is 1.5h -1The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 67% and the selectivity of acetaldehyde was 94%.
[0027] Example 9
[0028] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, the water content of the raw ethanol is 10wt%, and the mass space velocity of ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 73% and the selectivity of acetaldehyde was 90%.
[0029] Example 10
[0030] The preparation of 30wt% Cu-10wt% Sn-60wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 9.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 11.24g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 30wt% Cu-10wt% Sn-60wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 74% and the selectivity of acetaldehyde was 94%.
[0031] Embodiment 11
[0032] The preparation of 30wt% Cu-20wt% Sn-50wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 9.0g of copper nitrate trihydrate, 4.64g of tin tetrachloride pentahydrate and 9.37g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 30wt% Cu-20wt% Sn-50wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 75% and the selectivity of acetaldehyde was 96%.
[0033] Example 12
[0034] The preparation of 10wt% Cu-10wt% Sn-80wt% Al2O3 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 58.3g of aluminum nitrate nonahydrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% Al2O3 catalyst. Screen the catalyst with 14-25 mesh and fill it into the reaction tube, fill the 8cm bed, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 56% and the selectivity of acetaldehyde was 98%.
[0035] Embodiment 13
[0036] The preparation of 10wt% Cu-10wt% Sn-80wt% SiO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 2.32g of tin tetrachloride pentahydrate and 15.84g of 50wt% silica sol, disperse them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% SiO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed, and the mass space velocity of the raw ethanol is 1.5h -1The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 51% and the selectivity of acetaldehyde was 95%.
[0037] Embodiment 14
[0038] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts ball milling pyrolysis method. The specific operation is as follows: weigh 2.5g of copper acetate (200), 1.57g of tin acetate (237), and 15.0g of zirconium oxynitrate (231), mix and ball mill at 500r / min for 4h. After the end, collect the solid powder and dry it at 80℃ overnight. After calcining in air at 500℃ for 3h, 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst is obtained. The catalyst with a mesh size of 14-25 is filled into the reaction tube, and a 10cm bed is filled. The mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 68% and the selectivity of acetaldehyde was 99%.
[0039] Embodiment 15
[0040] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts ball milling pyrolysis method. The specific operation is as follows: weigh 2.5g of copper acetate (200), 1.57g of tin acetate (237), and 15.0g of zirconium oxynitrate (231), mix and ball mill at 500r / min for 4h. After the end, collect the solid powder and dry it at 80℃ overnight. After calcining in air at 500℃ for 3h, 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst is obtained. The catalyst with a size of 14-25 mesh is sieved and filled into the reaction tube. The 20cm bed layer is filled. The mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 78% and the selectivity of acetaldehyde was 91%.
[0041] Example 16
[0042] The preparation of 10wt% Cu-10wt% Sn-80wt% ZrO2 adopts ball milling pyrolysis method. The specific operation is as follows: weigh 2.5g of copper acetate (200), 1.57g of tin acetate (237), and 15.0g of zirconium oxynitrate (231), mix and ball mill at 500r / min for 4h. After the end, collect the solid powder and dry it at 80℃ overnight. After calcining in air at 500℃ for 3h, 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst is obtained. The catalyst with a size of 14-25 mesh is sieved and filled into the reaction tube. The 20cm bed layer is filled. The mass space velocity of the raw ethanol is 1.5h -1The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 78% and the selectivity of acetaldehyde was 91%.
[0043] Embodiment 17
[0044] The catalyst used in Example 1 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 10cm bed. The mass space velocity of the raw ethanol was 1.5h -1 The reaction was carried out at 300°C, and a sample was taken for chromatographic analysis after 2 hours of reaction. The conversion rate of ethanol was 57%, and the selectivity of acetaldehyde was 99%.
[0045] Embodiment 18
[0046] The catalyst used in Example 17 was collected and calcined in a muffle furnace at 500°C for 4 h, reduced with hydrogen at 300°C for 1 h, and filled into a reaction tube with a 10 cm bed. The mass space velocity of the raw ethanol was 1.5 h -1 The reaction was carried out at 300°C, and after 8 hours of reaction, a sample was taken for chromatographic analysis, and the conversion rate of ethanol was 59%, and the selectivity of acetaldehyde was 98%.
[0047] Embodiment 19
[0048] The catalyst used in Example 18 was collected and calcined in a muffle furnace at 500°C for 4 h, reduced with hydrogen at 300°C for 1 h, and filled into a reaction tube with a 10 cm bed layer. The mass space velocity of the raw ethanol was 1.5 h -1 The reaction was carried out at 300°C, and a sample was taken for chromatographic analysis after 10 hours of reaction. The conversion rate of ethanol was 57%, and the selectivity of acetaldehyde was 99%.
[0049] Embodiment 20
[0050] The catalyst used in Example 19 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into the reaction tube. The 10cm bed layer was filled, and the mass space velocity of the raw ethanol was 1.5h -1 The reaction was carried out at 300°C, and a sample was taken for chromatographic analysis after 18 hours of reaction. The conversion rate of ethanol was 61%, and the selectivity of acetaldehyde was 98%.
[0051] Comparative Example 1
[0052] The preparation of 10wt% Cu-90wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate and 16.88g of zirconium oxynitrate, dissolve them in 200ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-90wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 48% and the selectivity of acetaldehyde was 75%.
[0053] Comparative Example 2
[0054] The preparation of 10wt% Sn-90wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 2.32g of tin tetrachloride pentahydrate and 16.88g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Sn-90wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 31% and the selectivity of acetaldehyde was 90%.
[0055] Comparative Example 3
[0056] The preparation of 10wt% Cu-90wt% Al2O3 adopts the co-precipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate and 65.6g of aluminum nitrate nonahydrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-90wt% Al2O3 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling an 8cm bed layer, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 43% and the selectivity of acetaldehyde was 58%.
[0057] Comparative Example 4
[0058] The preparation of 10wt% Cu-90wt% SiO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate and 17.82g of 50wt% silica sol, disperse them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-90wt% SiO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer, and the mass space velocity of the raw ethanol is 1.5h -1 The reaction was carried out at 300°C. After 2 hours of reaction, the sample was taken for chromatographic analysis. The conversion rate of ethanol was 41% and the selectivity of acetaldehyde was 53%.
[0059] Comparative Example 5
[0060] The catalyst used in Comparative Example 1 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 10cm bed layer. The mass space velocity of the raw ethanol was 1.5h -1 The reaction was carried out at 300°C, and a sample was taken for chromatographic analysis after 10 hours of reaction. The conversion rate of ethanol was 34%, and the selectivity of acetaldehyde was 65%.
[0061] Comparative Example 6
[0062] The catalyst used in Comparative Example 5 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 10cm bed layer. The mass space velocity of the raw ethanol was 1.5h -1 The reaction was carried out at 300°C, and a sample was taken for chromatographic analysis after 10 hours of reaction. The conversion rate of ethanol was 31%, and the selectivity of acetaldehyde was 66%.
Claims
1. A method for preparing acetaldehyde by dehydrogenating ethanol, characterized in that: The process of preparing acetaldehyde by dehydrogenation of ethanol is as follows: ethanol is used as a raw material, a multiphase CuSn bimetallic catalyst is filled in a reaction tube, and a reaction is carried out in a fixed bed reactor at a reaction temperature of 250-450°C; The multiphase CuSn bimetallic catalyst is composed of Cu, Sn active metals and a carrier, wherein the active metal Cu content is 5 wt% to 35 wt%; the weight content of the metal Sn is 2% to 20%; The carrier is one or more of the oxides of Al, Zr and Si.
2. The method according to claim 1, characterized in that: The multiphase CuSn bimetallic catalyst is composed of Cu, Sn active metals and a carrier, wherein the carrier is one or two of the oxides of Al and Zr.
3. The method according to claim 1, characterized in that: The multiphase CuSn bimetallic catalyst has an active metal Cu content of 6 wt% to 25 wt% and a metal Sn content of 5% to 20%.
4. The method according to claim 1, characterized in that: The multiphase CuSn bimetallic catalyst has an active metal Cu content of 8 wt% to 15% and a metal Sn content of 6% to 15%.
5. The method according to claim 1, characterized in that: The catalyst bed thickness is 5 cm to 30 cm, the reaction is at normal pressure, and the feed mass space velocity of ethanol is 0.5 to 3.5 h -1 .
6. The method according to claim 1 or 5, characterized in that: The reaction conditions are as follows: the catalyst bed thickness in the reaction tube is 10 cm to 25 cm, the ethanol feed mass space velocity is 0.5 to 3.5 h -1 .
7. The method according to claim 1, characterized in that: The ethanol is anhydrous ethanol or an ethanol aqueous solution, and the water content is 1.0% to 10% by weight.
8. The method according to claim 1, characterized in that: The reaction temperature of the ethanol dehydrogenation to produce acetaldehyde is 280-330°C.
9. The method according to any one of claims 1 to 5, characterized in that: The catalyst is prepared by co-precipitation of Cu, Sn active metals and soluble salts corresponding to the carrier in a solution, or by ball milling and pyrolysis of Cu, Sn active metals and salts corresponding to the carrier.
Citation Information
Patent Citations
Method for producing glyoxylate through oxydehydrogenation of glycollate
CN107445830A
Preparation method for isopentyl aldehyde
CN1566056A